Photo-cross-linked dual-responsive hollow capsules mimicking cell membrane for controllable cargo post-encapsulation and release - Liu, Xiaoling; Appelhans, Dietmar; Wei, Qiang; Voit, Brigitte (Advanced Science, 2017)
Multifunctional and responsive hollow capsules are ideal candidates to establish highly sophisticated compartments mimicking cell membranes for controllable bio-inspired functions. For this purpose pH and temperature dual-responsive and photo-cross-linked hollow capsules, based on silica-templated layer-by-layer approach by using poly(N-isopropyl acrylamide)-blockpolymethacrylate) and polyallylamine, have been prepared to use them for the subsequent and easily available post-encapsulation process of proteinlike macromolecules at room temperature and pH 7.4 and their controllable release triggered by stimuli. The uptake and release properties of the hollow capsules for cargos are highly affected by changes in the external stimuli temperature (25, 37, or 45 °C) and internal stimuli pH of the phosphate-containing buffer solution (5.5 or 7.4), by the degree of photo-cross-linking, and the size of cargo. The photo-cross-linked and dual stimuli-responsive hollow capsules with different membrane permeability can be considered as attractive material for mimicking cell functions triggered by controllable uptake and release of different up to 11 nm sized biomolecules.
CRIS-Team Scopus Importer:2022-04-14